Tasmanian aborigines and muttonbirding : an historical examination - Skira, Irynej Joseph (1993)
The Tasmanian muttonbird, scientifically called the short-tailed shearwater Puffinus tenuirostris probably obtained its name because its flesh tasted like mutton. Over 80 percent of the world's population of 23 million birds breed in Tasmania, with the largest ' rookeries on the islands of Bass Strait. The bird has an egg-laying season of remarkable constancy enabling commercial exploitation to be carried out to a strict calendar. The term \muttonbirding\" defines the capture of the bird its killing and its processing into a product fit for human consumption. The remains of muttonbirds have been found in archaeological sites in Tasmania and mainland Australia but the meagre number present suggests that the birds were not an important food source to the Aborigines. In 1798 the seal colonies of Bass Strait were discovered and exploited by nonAboriginal sealers to near extinction. The sealers who remained took Aboriginal women for \"wives\". The population grew slowly based on a subsistence muttonbird economy. By 1872 the descendants of white sealer-Aboriginal women liaisons constituted just 40 percent of the total 27 4 people in the Fumeaux Group as immigrants took up leases of. islands once occupied by the descendants and eventually for~ed them onto Cape Barren Island. The area they settled on Cape Barren Island was 'declared a Reserve in 1881 and became an enclave requiring laws and government money to administer. Having very little income the annual harvesting of muttonbirds was the highlight of the year to these people. The immigrant settlers also looked to muttonbirding to sustain them through hard times and to pay off mortgagees. By the early 1900s up to 400 people participated in the annual season. In the 1920s catches of up to one million birds were recorded. Such a locally important industry required regulations to be frequently gazetted to conserve the birds for administrative purposes and to bring about hygiene in the presentation of the muttonbird for human consumption. The industry enticed some people ...